Attachment dan homesickness siswa baru di lingkungan Pondok Pesantren - Salmi, Nailatul Fadhila; Yasmin, Maya (PSYCOMEDIA : Jurnal Psikologi, 2023)
This research aims to describe the relationship between attachment and homesickness in new students at the Agam Regency Islamic boarding school. This study uses a quantitative approach. The population in this study were all new students at the Agam district Islamic boarding school, with a sample size of 322 people using a cluster sampling technique. Data collection used a scale with measuring instruments prepared by researchers based on the theories of Stroebe, Vliet, Hewstone, and Willis (2002) for the homesickness scale and Armsden & Greenberg (2009) for the attachment scale. Data analysis in research uses Pearson correlation techniques. The results of the analysis show that there is a relationship between attachment and homesickness, which statistically obtained a correlation coefficient of -0.424 and p = 0.01 (p<0.05). Keywords: homesickness, attachment, new students.